The importance of revisiting landform design after key decision-making events - Knight, K. (Mine Closure 2016: Proceedings of the 11th International Conference on Mine Closure, 2016)
URS Australia Pty Ltd (now AECOM Australia Pty Ltd) was commissioned to prepare technical specifications and oversee remediation works to construct a containment cell for the encapsulation of lead tailings at the Northampton State Lead Battery site in Western Australia. The design and construction works were conducted between September 2009 and January 2010 with the objective to reduce residual risks and long term liabilities associated with a safe, stable and non-polluting site. Design of the containment cell was to encapsulate an approximate volume of 20,000 m³ lead tailings. As the onsite work progressed, 14,000m³ of additional buried tailings materials were identified and, due to a lack of other suitable options, it was determined by the client and other relevant stakeholders that the additional volume of tailings had to be encapsulated within the same footprint. This altered the design of the cell significantly, which subsequently affected the desired rehabilitation outcomes. The scope did not allow for an alteration of rehabilitation methodology and consequently, three years post construction works, the landform showed signs of instability and the landform surface would not sustain vegetation. In 2013 a refocussed effort was made to promote achievable rehabilitation outcomes. Despite various technical challenges such as steep batters, lack of growth medium, and challenging climatic conditions, these rehabilitation efforts have been successful; the landform is currently safe, stable, non-polluting, and is on a path towards hosting self sustaining vegetation. As a result, a collaborative technical approach, inclusive of engineers, hydrologists, geotechnical and rehabilitation specialists has become an important component of all URS remediation projects.
Keywords: landform design; rehabilitation decision making and outcomes; collaborative technical approach